The San Rafael Lagoon Hotel, the Ofqui channel and the opening of the western patagonian borderland: city, architecture and landscape in the state discourse (REVISTA NODO, 2021)
This paper approaches the relationships between architecture, city and landscape through the process of opening the southern borderland of Chile, while emphasizing the ideas that tried to turn the environment of the Isthmus of Ofqui into a new center of development, as the main port of the central Patagonia. The paper starts recognizing the value of the landscape, composed by the sea, fjords, canals, lagoon and San Rafael glacier, which together constitutes tourism potential of a world scale. There, in the middle of hundreds of kilometers of uninhabited coast, ending the 30s, a hotel was built, conceived as visual and chromatic continuity with the environment and evocating the landscape of the glacier by the horizontal fringes of its faces. The importance of the hotel, beyond its intrinsic architectural value, lies in the confidence with which the state conceived its construction as the spearhead of the colonization of the whole southern coast, starting from the urbanization of its immediate environment and as the base for the resignification of a territory previously considered as inhospitable.
Keywords: Architecture; City; Landscape; Borderland; Connectivity